2016
DOI: 10.1111/jnc.13767
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid receptor interacting protein suppresses agonist‐driven CB1 receptor internalization and regulates receptor replenishment in an agonist‐biased manner

Abstract: Cannabinoid receptor interacting protein 1a (CRIP1a) is a CB1 receptor (CB1R) distal C-terminus-associated protein that modulates CB1R signaling via G proteins, and CB1R down-regulation but not desensitization (Blume et al. [2015] Cell Signal., 27, 716–726; Smith et al. [2015] Mol. Pharmacol., 87, 747–765). In this study, we determined the involvement of CRIP1a in CB1R plasma membrane trafficking. To follow the effects of agonists and antagonists on cell surface CB1Rs, we utilized the genetically homogeneous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Thus, we cannot rule out the possibility that if CRIP1a bound to the CB 1 R precludes a CB 1 R-Gi3 or Go complex, then a subsequent phosphorylation and interactions with b-arrestin might not be initiated. In studies of the agonist-mediated depletion of cell surface CB 1 R, we found that CRIP1a overexpression prevented CB 1 R internalization (Blume et al, 2016). This finding is completely consistent with a competition by CRIP1a for a binding site for b-arrestin on the CB 1 R C-terminal and the amelioration of the b-arrestinmediated internalization processes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Thus, we cannot rule out the possibility that if CRIP1a bound to the CB 1 R precludes a CB 1 R-Gi3 or Go complex, then a subsequent phosphorylation and interactions with b-arrestin might not be initiated. In studies of the agonist-mediated depletion of cell surface CB 1 R, we found that CRIP1a overexpression prevented CB 1 R internalization (Blume et al, 2016). This finding is completely consistent with a competition by CRIP1a for a binding site for b-arrestin on the CB 1 R C-terminal and the amelioration of the b-arrestinmediated internalization processes.…”
Section: Discussionsupporting
confidence: 82%
“…2B). The clustering of GFP-CB 1 R in the CRIP1a XS cells before agonist stimulation is a phenomenon that will require greater investigation, because data from our studies of exposure to agonist ligands suggest that CRIP1a could play an inhibitory role in trafficking of the CB 1 R to the plasma membrane (Blume et al, 2016). Exposure to CP55940 (10 nM, 15 minutes) resulted in a pronounced redistribution of GFP-CB 1 R fluorescence into discrete punctate aggregates along the membrane surface in WT and empty-vector control cells.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…), which can be inhibited by CRIP1a in the N18TG2 cell line (Blume et al . ,b). To analyze in detail underlying molecular mechanisms using a previously established internalization assay in HEK293 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CRIP1a plays a role in the control of agonist-driven CB 1 R cell surface regulation by competing with β-arrestins and thereby attenuating agonist-mediated internalization[14,15]. CRIP1a over-expression attenuated the agonist-induced redistribution of endogenous β-arrestin to punctae aggregates and subsequent loss of cell surface CB 1 receptors.…”
Section: Introductionmentioning
confidence: 99%